The Development Of Student Worksheets (LKS) With A Contextual Approach To Arrithmetic And Geometry Sequences - Anny Zuliyana; muhammad Aminuddin (INOVASIA, 2022)
This research is development research that aims to produce Student Worksheets (LKS) with a valid and practical contextual approach so that it is suitable for use in the learning process on arithmetic and geometric sequences. The development design used in this study is the ADDIE development model, which consists of five stages, namely 1) the analysis stage, 2) the planning stage, 3) the development stage, 4) the implementation stage, and 5) the evaluation stage. Based on the data analysis results, the following results were obtained (1) the level of validity got a score of 3.3 with very valid validity criteria, (2) the level of practicality got a score of 3.9, with efficient criteria of practicality. Therefore, it can be concluded that the developed worksheets meet the good criteria so that they are suitable to be used as one of the teaching materials that can be used in Arithmetic and Geometry Sequences.